Police Disregard of Public Complaints: A Juridical Review of Article 13 and Article 14 Paragraph (1) Letter g of Law No. 2 of 2002 from the Perspective of Islamic Criminal Law - Ridwan Setiawan; Yayan Muhammad Royani; Muhamad Kholid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study is motivated by the increasing number of public complaints regarding the neglect of reports by police officers, which has implications for obstructing access to justice, even though Law Number 2 of 2002 emphasizes the function of the Indonesian National Police as protectors, guardians, and public servants. This study aims to analyze the legal obligations of police officers in receiving and following up on public complaints based on Article 13 and Article 14 paragraph (1) letter g, the forms of legal accountability for the neglect of such complaints, and to examine them from the perspective of Islamic criminal law. The method used is normative juridical research with statutory, conceptual, and comparative approaches, based on library research of legislation, academic literature, and sources of Islamic law. The results show that, normatively, police officers have an imperative legal obligation to receive and follow up on public complaints; however, the mechanisms of administrative, ethical, and criminal accountability for neglecting these obligations remain weak in practice. From the perspective of Islamic criminal law, the neglect of complaints is viewed as a violation of trust (amanah), contrary to the principle of justice (‘adl), and constitutes a form of wrongdoing (zulm) that may be classified as a ta’zir offense subject to sanctions. This study contributes to strengthening the normative and ethical foundations for enforcing police obligations in handling public complaints.